Do clinical features and MRI suggest the same nerve root in acute cervical radiculopathy - M. Conradie; M. M. Bester; L. C. Crous; M. Kidd (AOSIS, 2006)
Different proposed pathophysiological mechanisms can result in variable clinical presentations of cervical radiculopathy (CR), often making it difficult to detect minor nerve root (NR) conditions. This descriptive study determined (1) the level(s) of  NR involvement suggested by the distribution patterns of clinical features and detected by magnetic resonance imaging (MRI) and (2) the most common associations between the different variables in patients diagnosed with acute CR by a neurosurgeon. A physiotherapist blinded to the level(s) of NR involvement performed a standardized interview on 21 subjects to determine the distribution patterns of pain and paraesthesia, and a neurological examination. The Fisher exact test was used to determine associations between the different variables. Only seven subjects presented clinically and radiologically with the same single-level NR involvement. Multiple- level presentations occurred which might be due to dermatomal overlapping, central sensitization or the possible involvement of two adjacent NR levels. Distribution patterns of motor weakness, pain and paraesthesia, and to a lesser extent sensory and reflex changes, have value in identifying the compressed NR level. For this sample the distri-bution patterns of radicular features identified C6 and C8 with more certainty than C7.